PSYCHOSOCIAL FACTORS ASSOCIATED WITH MAJOR THALASSEMIA - Al_Hamadiny, Shahad Qasim; Alqaisi, Ali Abbas Sadiq; Al-Sarray, Riyam Ghazi Kareem; Ali, Sarah Akar; Trad, Hawraa Qasim; Abood, Ali Jalal (PT. Antis International Publisher, 2024)
Thalassemia is a hereditary condition that results in the creation of defective haemoglobin molecules. Patients are diagnosed with thalassemia major after exhibiting severe clinical symptoms and profound anaemia. This study aims to investigate the major thalassemia and psychosocial aspects of it, which is a critical issue, in order to serve as a road map for better treating these patients and contribute to the literature. This study used narrative review as its method. Between 2018 and 2023, a literature review was undertaken by searching materials published in databases such as Web of Science, PubMed, Scopus, and the Google Scholar search engine. Additionally, the WHO website was searched. Thalassemia major harms the heart, liver, lungs, and endocrine organs due to anaemia and iron buildup. Furthermore, the patient could experience. Mental and social issues arise as a result of the disease's congenital aetiology and lifelong duration. Thalassemia patients face significant emotional challenges as well as therapeutic burden. There are numerous research on the prevalence and physical implications of thalassemia. However, there are insufficient papers and studies documenting the psychosocial impacts of thalassemia on patients and what may be done to mitigate these effects. As a result, this research focuses on the process of thalassemia and the psychosocial problems it causes in order to contribute to the literature and provide a road map for better managing these individuals